(untitled) (Trabalho & Educação, 2018)
Since the end of the 1970’s, three structural mutations of economy have affected the conditions for creating the value of work: the driving force of services, the generalisation of ntic and the strategic aspect of the immaterial dimensions of resources and products. Within this new framework, the stakes of work are different from those of the industrial era and are associated with the upsurge of subjectivity and intersubjectivity. From this perspective, the vision of the economic performance and of its modes of evaluation will be revisited; the economy of time as well. These two approaches to analysis will feed the critic against institutional devices from the last thirty years and will raise the key question of the emergence of new institutional devices, which are relevant and legitimate in view of the stakes of real work and of the dynamics of "services economy".